Design of functionalized cyclic peptides through orthogonal click reactions for cell culture and targeting applications. Issue 50 (4th June 2018) - LeValley, Paige J.; Ovadia, Elisa M.; Bresette, Christopher A.; Sawicki, Lisa A.; Maverakis, Emanual; Bai, Shi; Kloxin, April M.
Abstract : An approach for the design of functionalized cyclic peptides is established for use in 3D cell culture and in cell targeting. Abstract : An approach for the design of functionalized cyclic peptides is established for use in 3D cell culture and in cell targeting. Sequential orthogonal click reactions, specifically a photoinitiated thiol–ene and strain promoted azide–alkyne cycloaddition, were utilized for peptide cyclization and conjugation relevant for biomaterial and biomedical applications, respectively.